2021
DOI: 10.5498/wjp.v11.i12.1387
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID-19 pandemic on individuals with serious mental disorders: A systematic review of the literature

Abstract: BACKGROUND The coronavirus disease 2019 (COVID-19) pandemic is having a great impact on individuals from all over the world, particularly on individuals with mental disorders. Several studies found more pronounced psychiatric symptoms, notably symptoms of depression and anxiety. AIM To assess the situation of patients with serious mental illness (SMI: Affective disorders and schizophrenia) regarding their mental health outcome during the pandemic. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 97 publications
3
31
0
1
Order By: Relevance
“…Regarding UPCs in ER, we highlighted that living in a psychiatric facility or community is a factor associated with an increase of UPC during pandemic but not suffering from most psychiatric disorders or being treated in outpatient service, which, on the contrary, represent detrimental factors for UPC in outbreak. These results further identify in people already affected by a severe mental disorder the population most psychologically vulnerable to socio-environmental distress induced by COVID-19, as highlighted by other authors ( 68 ). We confirmed that the month of March 2020 was a detrimental factor for the number of UPCs in ER.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding UPCs in ER, we highlighted that living in a psychiatric facility or community is a factor associated with an increase of UPC during pandemic but not suffering from most psychiatric disorders or being treated in outpatient service, which, on the contrary, represent detrimental factors for UPC in outbreak. These results further identify in people already affected by a severe mental disorder the population most psychologically vulnerable to socio-environmental distress induced by COVID-19, as highlighted by other authors ( 68 ). We confirmed that the month of March 2020 was a detrimental factor for the number of UPCs in ER.…”
Section: Discussionsupporting
confidence: 81%
“…This could suggest that the subjects with more mental problems had some difficulties in undertaking a treatment program during the pandemic. Indeed, the SARS-CoV-2 pandemic had notoriously accentuated stress, anxiety, and depression in the general population [27], particularly in subjects with previous psychiatric symptomatology [28]. The comparison between patients visited during and outside the pandemic period (Supplementary Table S1) confirmed that depression and anxiety may have impacted the search for treatment during the pandemic in subjects with more psychiatric symptomatology.…”
Section: Discussionmentioning
confidence: 78%
“…A recent review showed an increase of psychiatric symptoms e.g. anxiety, depression and stress in individuals with AD during the pandemic [59] . Especially people with a low socioeconomic environment, lack of social support, inadequate information about COVID-19 and a shortage in mental health-services showed a mental-wellbeing impairment.…”
Section: Discussionmentioning
confidence: 99%